Lectores, cátedras y libros: prácticas y costumbres universitarias en el convento de Santo Domingo de Santiago de Chile durante el siglo XVII - Miguel Lecaros Álvarez (Centre de Recherches sur les Mondes Américains, 2017)
The historiography of chilean colonial universities does not exceed forty books and articles, and mainly deals with institutions in Santiago. Nevertheless, they have frequently left to one side the scholars, their practices and their libraries, among other topics, probably due to the difficulty to access the ecclesiastical archives. In this article, we draw a short historiographical report of the colonial universities of Chile. Then, we present scholar practices through three criteria: chairs, readers and the bookshelf. This study was made within the scope of a larger research that allowed the consultation of various book collections.